The Current Strategy in Managing Congenital and Structural Heart Disease: Find and Treat Them Appropriately - Prakoso, Radityo (Universitas Brawijaya, 2024)
Significant progress has been made in diagnosing and treating congenital heart defects (CHDs) over the past five decades. Notable advancements include pulse oximetry screening for critical CHDs in newborns and percutaneous, catheter-based procedures, improving outcomes even in developing nations. Recent studies demonstrate favorable outcomes with device closure of acyanotic CHDs, with non-fluoroscopy techniques adopted to minimize radiation risks. Positive results are observed with right ventricular outflow tract (RVOT) stent palliation for late-presenting cyanotic congenital heart diseases such as tetralogy of Fallot (TOF). Novel interventions like reverse Potts shunt anastomosis show promise in managing pediatric pulmonary arterial hypertension (PAH), while prophylactic treatments effectively reduce postoperative arrhythmias. Fontan procedure significantly enhances survival rates for individuals with single functional ventricles, although challenges arise with aging populations. In developed countries, fetal cardiac interventions utilizing advanced imaging techniques allow for early detection and preventive interventions, reducing secondary complications.